The Effectiveness of E-Learning Based Mathematics Learning on High School Students' Learning Outcomes - Zulaiha, Zulaiha (Journal Corner of Education, Linguistics, and Literature, 2024)
The purpose of this study is to ascertain how well e-learning-based learning models affect the learning outcomes of high school mathematics students. Using a nonequivalent control group design, a quantitative, quasi-experimental methodology is employed. Two XI classes, each with 30 students, during the 2024-2025 school year at State Senior High School 10 Bandar Lampung made up the sample. While the control group employed traditional learning methods, the experimental group employed e-learning-based learning. A multiple-choice learning outcome test that has undergone reliability testing and validation served as the tool. With a significance value of 0.001 (p <0.05), the data analysis results demonstrated that the experimental group's average mathematics learning outcomes (78.60) were substantially greater than the control group's (71.40). The results of the precondition test demonstrated that the data had homogeneous variance and were normally distributed. These results suggest that interactive media, enhanced learning motivation, and flexibility of access are ways that e-learning can enhance student learning outcomes. As a result, e-learning-based math instruction may be a wise choice for raising educational standards in the digital age.